The Amazon from an international law perspective / Beatriz Garcia. - Garcia, Beatriz, 1974- (Cambridge University Press, 2011)
With a vast river network and rainforests extending over eight South American countries, the Amazon plays a vital role particularly in maintaining biodiversity and terrestrial carbon storage. Due to its ecological characteristics, the Amazon benefits not only those countries but also the international community at large. However, the Amazon forests are being rapidly cleared with a consequent loss of biodiversity and impact on global climate. This book examines whether international law has an impact on the preservation of the Amazon by inquiring into the forms of cooperation that exist among the Amazon countries, and between them and the international community, and to what extent international cooperation can help protect the Amazon. Given the role of this region in maintaining the balance of the global environment, the book examines whether the Amazon should be granted a special legal status and possible implications in terms of international cooperation.